2020
DOI: 10.2147/dddt.s281582
|View full text |Cite
|
Sign up to set email alerts
|

<p>Agomelatine Attenuates Isoflurane-Induced Inflammation and Damage in Brain Endothelial Cells</p>

Abstract: Background and Purpose Neurotoxicity of anesthetics has been widely observed by clinicians. It is reported that inflammation and oxidative stress are involved in the pathological process. In the present study, we aimed to assess the therapeutic effects of agomelatine against isoflurane-induced inflammation and damage to brain endothelial cells. Materials and Methods MTT assay was used to detect cell viability in order to determine the optimized concentration of agomelat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 39 publications
1
5
0
Order By: Relevance
“…Anesthetics can also promote the release of inflammatory cytokines. ISO causes the accumulation of several inflammatory regulators, such as TNF-α [26]. Our conclusion also identified this point by that ISO increased the concentration of TNF-α, IL-6, and IL-1β.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…Anesthetics can also promote the release of inflammatory cytokines. ISO causes the accumulation of several inflammatory regulators, such as TNF-α [26]. Our conclusion also identified this point by that ISO increased the concentration of TNF-α, IL-6, and IL-1β.…”
Section: Discussionsupporting
confidence: 75%
“…As a new type of inhalation anesthetic, ISO is widely used in clinical surgery because of its high safety and controllability [26]. In recent years, it has been found that ISO is potentially harmful to the brain of developing mammals by producing persistent neurocognitive dysfunction after ISO anesthesia [27].…”
Section: Discussionmentioning
confidence: 99%
“…Then, the anti-inflammatory activity of agomelatine was studied. The previous report revealed that agomelatine intervention could alleviate isoflurane-induced inflammation by decreasing the level of IL-6, IL-8, TNF-α, VCAM-1, and ICAM-1 in brain endothelial cells ( Cheng et al, 2020 ). Hans O. Kalkman also indicated that agomelatine suppressed inflammation and M1-microglial polarization via modulating IGF1 expression ( Kalkman and Feuerbach, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Our previous study also found that after agomelatine intervention, tau protein hyperphosphorylation and oxidative injury obviously decreased in Aβ 25–35 -treated BV-2 cells ( Yao et al, 2019 ). Besides, some recent studies suggested that agomelatine may exert anti-inflammatory properties in vitro and in vivo ( Cheng et al, 2020 ; Savran et al, 2020 ). Although less evidence has focused on the effect of agomelatine in AD therapy, there are also limitations.…”
Section: Introductionmentioning
confidence: 99%
“…After 12 h, the cells were given the different concentrations of dioscin (0, 72, 145, 290, 580 and 1160 nM) under 6, 12 and 24 htreatment. Cell viabilities were conducted by MTT method as described above and a suitable concentration of dioscin was optimized [ 34 ].…”
Section: Methodsmentioning
confidence: 99%